Enhancing the effectiveness of the Health Star Rating via presentation modifications - Simone Pettigrew; Liyuwork Dana; Zenobia Talati (Elsevier, 2020)
Abstract Objective: Research demonstrates the superiority of highly interpretive front‐of‐pack nutrition labels. The aim of this study was to assess the potential to enhance the Health Star Rating (HSR) by increasing its 'interpretiveness' through the addition of colour and the exclusion of the nutrient icons. Methods: An online survey was administered to 1,033 Australian adults who were randomly allocated to one of four conditions: black and white (B&W) full HSR, colour full HSR, B&W star rating only, and colour star rating only. Each respondent viewed four packs of breakfast cereal of varying levels of healthiness as indicated by the displayed HSRs. Respondents nominated the product option they would prefer to buy and then the one they understood to be healthiest. Results: Coloured HSR variations scored better than their B&W counterparts and the star‐only versions scored better than the corresponding versions displaying nutrient icons. Overall, the coloured star‐only HSR performed significantly better than the B&W full HSR for both choice and understanding. Conclusions: Increasing the interpretive nature of the HSR could enhance its effectiveness. Implications for public health: Policy makers should consider the evolution of the HSR towards a more interpretive presentation that includes colour and excludes the nutrient icons.